Applied microbiology for nurses - Gould, Dinah; Brooker, Christine (Basingstoke : Macmillan Publishing Company, 2000)
This resource offers a comprehensive and accessible introductory text that demystifies microbiology for students and practicing nurses. It demonstrates clinical relevance and practical realities throughout, and includes such carefully designed features and aids designed to help students consolidate and retain their knowledge.
Preface -- Foreword -- Acknowledgements -- 1. Micro-Organisms and Disease -- 2. Response of the Body to Infection -- 3. The Microbiology Laboratory -- 4. Treating Infectious Disease -- 5. Infection Control Policies -- 6. Preventing Infection in Hospital -- 7. Urinary Infections -- 8. Wound Infections -- 9. Respiratory Infections -- 10. Infections Associated with Intravascular Devices -- 11. Enteric Infections -- 12. Infection Risks from Blood and Body Fluids -- 13. Sexually Transmitted Infections -- 14. Epidemiology: Changing Trends of Infectious Diseases -- Glossary.
Includes bibliographical references and index.
Keywords: MEDICAL MICROBIOLOGY